РУССКАЯ ЛИТЕРАТУРА XIX-XX ВЕКОВ В КОНТЕКСТЕ БОЛЬШОГО ВРЕМЕНИ (Philological Studies, 2019)
XIX-XX century Russian literature boundary metatext is considered as a sense originating context of mental values.